Dietary intake of carotenoids and fiber is inversely associated with aggression score in adolescent girls. Issue 3 (September 2019) - Khayyatzadeh, Sayyed Saeid; Firouzi, Safieh; Askari, Maral; Mohammadi, Farzane; Nikbakht-Jam, Irandokht; Ghazimoradi, Maryam; Mohammadzadeh, Mohammad; Ferns, Gordon A; Ghayour-Mobarhan, Majid
Background: Violence and aggression are considered to be important public health issues. There is limited data on the association between dietary intake and aggression score. Aim: We aimed to examine the relationship between the dietary intake and aggressive behavior in Iranian adolescent girls. Methods: The study was carried out among 670 girls aged 12–18 years. A valid and reliable food frequency questionnaire (FFQ) containing 147 food items was used to estimate dietary intake of the study participants. Aggression score was determined using a validated Persian version of the Buss–Perry questionnaire. We analyzed our data using crude and adjusted models. Results: Participants in the fourth quartile of aggression score had significantly higher energy intake compared with those in the first quartile (2808±949 vs 2629±819, p -trend = 0.01). Dietary intakes of soluble fiber (0.42±0.37 vs 0.35±0.29, p = 0.03) and insoluble fiber (2.17±1.65 vs 1.82±1.36, p = 0.02) were significantly higher in the first quartile than in the fourth quartile. In addition, the strongest negative correlations were found between aggression score and dietary soluble fiber ( p = 0.003) and insoluble fiber intake ( p = 0.001). Moreover, aggression score was negatively correlated with dietary α-carotene ( p = 0.02) and β-carotene ( p = 0.04) intake. These associations remained significant even after adjustment for potential confounders. Conclusions: Our results indicated that dietary intakes of fiber, α-carotene, and β-carotene were inversely associated with aggression score. Moreover, a significant positive association was observed between energy intake and aggression score in adolescent girls.